Posttraumatic Avascular Necrosis of the Talus: Prevention, Course, and Treatment Options - Kopp, Lubomir; Rammelt, Stefan (Foot and ankle clinics, 2025)
Avascular necrosis (AVN) of the talus in a posttraumatic setting describes a condition of temporary or permanent bone death of a different extent, initiated by a circulatory disturbance. It is estimated that about 75% of all talar AVNs are caused by a prior trauma. The incidence of posttraumatic AVN rises with higher energy of injury, severity of talar body or neck displacement, fracture comminution, and injury to the soft tissues and major vessels in the lower leg and ankle region. These conditions are often seen in open fractures, fracture dislocations, and pure dislocations.
Keywords: Talus; Fracture; Malunion; Necrosis; osteonekróza; Replacement; Fusion; lidé; poranění kotníku; talus; Ankle Injuries; Osteonecrosis; Vascularized bone graft; Nonunion; Humans